New York Paper - Composition of Petroleum and its Relation to Industrial Use (with Discussion) - C. F. Mabery (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
So far as the elementary composition of petroleum is known, it may be briefly stated. Petroleum consists principally of a few series of hydrocarbons, with admixtures of sulfur, nitrogen, and oxygen derivatives in comparatively minute proportions, which may be regarded as impurities to be removed in the preparation of commercial products. But as each series is represented by many homologs, in the aggregate, crude petroleum is an extremely complex mixture of hydrocarbons and their derivatives. In part, these hydrocarbons individually conform in structure to the system of synthetic hydrocarbons whose structure is well defined and represented by the typical series CnH2n, + 2, C.H2n, the series CnH2n,-2, CnH2,-a, the members of which have not been sufficiently studied to establish their structure, and the series CnHz,e composed of the aromatic group, benzene and its homologs. Hydrocarbons of greater density contained in the portions of petroleum that cannot be distilled without decomposition doubtless have less hydrogen than is represented by these formulas. Since to every hydrocarbon there is a definite temperature, even in vacuum, at which its constituent carbon and hydrogen atoms fall apart, and since for the heavier bodies this temperature is not much above 360" C. in vacuum, it is evident that some other method than distillation must be devised for their separation if anything further is to be learned concerning their individual constitution. Classification of Petroleums There is such a wide variation in the composition of petroleum from Merent fields, it would seem possible to make a classification on this basis were it not that no single variety is entirely free from hydrocarbons contained in others. Such a classification has been suggested of the exceptionally pure Pennsylvania petroleum, the sulfur oil from Trenton limestone and other sources, the California oil with its large amount of nitrogen (quinoline) derivatives, and the Russian oil, composed chiefly of the naphthene hydrocarbons.' A commercial distinction is made